A framework for the development of learning management systems for higher education institutions in the Kingdom of Saudi Arabia - Alduraywish, Yousef Ahmed Y (Cranfield University, 2020)
This study focuses on a framework for the development of the Learning Management System (LMS) in the Kingdom of Saudi Arabia (KSA) higher education institutes (HEIs) from information systems (IS) perspective, using the Technology Acceptance Model (TAM) and Design Reality Gap (ITPOSMO) model. The research methodology consists of six stages which adopts the paradigm of pragmatism and the research design of mixed-methods. A case study design is used to investigate the implementation of LMS in the Al-Imam Mohamed bin Saud Islamic University. The quantitative part was designed to investigate the attitude of users towards the usefulness of the LMS and to assess the acceptance level of LMS among university users. The qualitative part was designed to explore the gap between the proposed implementation of the LMS and reality. The survey received valid responses from 129 academic and 1548 student. A semistructured interviews with 21 participants. The sample was achieved via a purposive sampling technique. The quantitative data was analysed using descriptive statistical analysis and correlation coefficient. The qualitative data were analysed using a thematic analysis approach. The study identifies the barriers influencing effective LMS in KSA HEIs as 1) technology barriers (lack of IT infrastructure, incomplete functionalities and lack of integration); 2) human barriers (lack of knowledge of the importance of elearning, lack of expertise and competencies); and 3) organisation barriers (organisational preparedness, unclear of requirements, lack of training, resistance and financial constraints). The contribution of this research includes a new model derived from the ITPOSMO model and TAM to investigate LMS in the context of real circumstances, and the physical environment that exists in KSA HEIs. The research focus is more on meso level while encompassing first and third levels as reference for better understanding (Richter et al., 2009). The results lead to developing a framework for the development of LMS in KSA HEIs.
Keywords: Information Systems; Learning Management System; Critical success factor; Key barriers; Stakeholders requirements; Technology Acceptance Model (TAM); Design Reality Gap (ITPOSMO) model; Interpretive Structural Modelling (ISM); a framework for the development of LMS; Kingdom of Saudi Arabia (KSA)